Dynamic Convergence as a Moderating Force: Entrepreneurial Orientation, Employee Performance, and the Pursuit of Firm Agility - Soewitoardjo, Rendy; Kaihatu, Thomas Stefanus; Herdinata, Christian (International Review of Management and Marketing, 2026)
Firm agility has emerged as a critical organisational capability in environments characterised by competitive intensity and rapid technological disruption, yet the mechanisms through which entrepreneurial orientation (EO) generates agility and individual performance outcomes remain theoretically underspecified. This study develops and tests a moderated mediation framework wherein EO influences employee performance both directly and indirectly through firm agility as a mediating conduit, with dynamic convergence defined as the degree to which generationally diverse cohorts achieve integrative alignment in adaptive values and collaborative practices moderating the agility–performance relationship. Grounded in Dynamic Capabilities Theory and the Resource-Based View, six hypotheses are tested using PLS-SEM combined with Necessary Condition Analysis (NCA) on a dyadic manager–employee dataset of 300 matched pairs from Indonesian SMEs. Results confirm that EO exerts a dominant direct effect on firm agility and a moderate direct effect on employee performance, while firm agility partially mediates the EO–performance pathway. Dynamic convergence amplifies the agility–performance relationship and satisfies necessity thresholds alongside EO and firm agility. The study contributes by establishing dynamic convergence as a theoretically grounded boundary condition and demonstrating that firm agility constitutes the most binding necessary prerequisite for superior employee performance in emerging-market SME contexts